2019
DOI: 10.1108/maj-01-2018-1767
|View full text |Cite
|
Sign up to set email alerts
|

Financial fraud detection and big data analytics – implications on auditors’ use of fraud brainstorming session

Abstract: Purpose This paper aims to discuss the application of Big Data analytics to the brainstorming session in the current auditing standards. Design/methodology/approach The authors review the literature related to fraud, brainstorming sessions and Big Data, and propose a model that auditors can follow during the brainstorming sessions by applying Big Data analytics at different steps. Findings The existing audit practice aimed at identifying the fraud risk factors needs enhancement, due to the inefficient use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 64 publications
2
45
0
14
Order By: Relevance
“…Analyzing this structured data further enables companies such as banks to detect fraudulent activities. Tang and Karim (2019) reveal that dig data analytics help strengthen results, identify fraud indicators, and document current issues in banks. This fraud detection theme has also been recognized by researchers in the context of big data and listed in the content analysis table.…”
Section: Research Themesmentioning
confidence: 99%
“…Analyzing this structured data further enables companies such as banks to detect fraudulent activities. Tang and Karim (2019) reveal that dig data analytics help strengthen results, identify fraud indicators, and document current issues in banks. This fraud detection theme has also been recognized by researchers in the context of big data and listed in the content analysis table.…”
Section: Research Themesmentioning
confidence: 99%
“…Many studies documented the benefit of using a combination of structured and unstructured data in audit evidence (Janvrin & Weidenmier Watson, 2017;Astami et al, 2017). Tang and Karim (2019) found that an auditor's use of unstructured data is still limited and thus recommended upgrading the practitioners' skills to manage the data variety, velocity, volume, veracity, and value. Because the benefits of big data use in the auditing process could vary based on the precise time used, the use of big data interpretation, as having been documented, provides better advantages if used after evaluating the traditional audit evidence (Rose et al, 2017).…”
Section: Emerging Technologies In Auditing and Assurancementioning
confidence: 99%
“…According to the existing relevant researches [22,23], this paper selects the appropriate financial indicators from nine categories of profitability, operating capacity, development capacity, per share index, ratio structure, solvency, risk level, disclosure of financial indicators, and cash flow analysis as the features of financial fraud identification.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%